Synthesis Of Some New Heterocyclic Compounds - I.C.SHUKLA,; OM PRAKASH YADAV,; VINOD KUMAR,; SANJAI KUMAR, (International Journal of Pharma and Bio Sciences, 2011)
Synthesis of substituted heterocyclic compounds has been done by smiles rearrangement by substituted 2-amino-2’-nitrodiphenylsulphides.The later are produced by the formylation of substituted 2-amino-2’-nitrodiphenylsulphides, which are prepared by the condensation of 2-aminobenzenethiols with substituted o-halonitrobenzenes.